OBE-Based Education Crisis Communication Strategy After the Covid-19 Pandemic - Faustyna Faustyna (RIRAI Publisher, 2023)
The phenomenon of graduates who are by their specialization while studying at institutions or schools or universities often occurs that is different from the jobs they get in the outside environment or the company where they work. Many even cannot get jobs because they are not by their education. The author aims to carry out this research to identify and describe how institutions integrate education through media and OBE (outcome-based education) to create appropriate graduates according to the crisis communication strategy. Data collection uses descriptive-qualitative methods based on Situational Crisis Communication Theory (SCCT), and data are collected through documents in the form of workplace phenomena related to media and technology integration. The results of this study indicate that the education provider uses a crisis communication strategy in the implementation of education associated with the integration of media and technology. Conclusion of the process of educational institutions using crisis communication strategies through transparency, crisis teams, social media integration, psychological support and evaluation in learning in higher education institutions.